2021
DOI: 10.3389/fmicb.2021.738617
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Nep1-Like Protein Effectors of the Necrotrophic Pathogen – Alternaria brassicae

Abstract: Alternaria brassicae is an important necrotrophic pathogen that infects the Brassicaceae family. A. brassicae, like other necrotrophs, also secretes various proteinaceous effectors and metabolites that cause cell death to establish itself in the host. However, there has been no systematic study of A. brassicae effectors and their roles in pathogenesis. The availability of the genome sequence of A. brassicae in public domain has enabled the search for effectors and their functional characterization. Nep1-like p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…The low, but increasing levels of gene expression of the Cc_NLP1.2B gene may be due to a time-increasing gene expression cascade. It agrees with the hypothesis of redundancy of NLP copies as a strategy of functional diversification to overcome the host surveillance in a time-dependent manner (Seidl et al 2015; Duhan et al 2021; Dal’Sasso et al 2022). The NLP encoding-genes are usually expressed in the early hours of host colonization but their expression could follow up to days, depending on the time needed by the pathogen to penetrate the host tissue (Levin et al 2019; Pour et al 2020; Duhan et al 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The low, but increasing levels of gene expression of the Cc_NLP1.2B gene may be due to a time-increasing gene expression cascade. It agrees with the hypothesis of redundancy of NLP copies as a strategy of functional diversification to overcome the host surveillance in a time-dependent manner (Seidl et al 2015; Duhan et al 2021; Dal’Sasso et al 2022). The NLP encoding-genes are usually expressed in the early hours of host colonization but their expression could follow up to days, depending on the time needed by the pathogen to penetrate the host tissue (Levin et al 2019; Pour et al 2020; Duhan et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…It agrees with the hypothesis of redundancy of NLP copies as a strategy of functional diversification to overcome the host surveillance in a time-dependent manner (Seidl et al 2015; Duhan et al 2021; Dal’Sasso et al 2022). The NLP encoding-genes are usually expressed in the early hours of host colonization but their expression could follow up to days, depending on the time needed by the pathogen to penetrate the host tissue (Levin et al 2019; Pour et al 2020; Duhan et al 2021). Taken together, our gene expression analyses suggested that the expression of the NLP effector genes may occur in different levels during host colonization; likely, not all NLP effector genes are essential for pathogenicity of C. cassiicola to soybean.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we found that the non-cytolytic activity of CaNLPs resulted from substitution of the KD motif and the heptapeptide motif GHRHDWE, and changes of structure characteristics lead to significant differences in the strength of necrosis-inducing activity between CaNLPs. Similar results have been reported in the necrotrophic pathogen Alternaria brassicae ( Duhan et al, 2021 ). Additionally, the responses of plants to NLPs not only depend on the type of NLP, but also the plant species in which the responses are tested.…”
Section: Discussionsupporting
confidence: 89%
“…Several different approaches have been implemented to explore the cell death-inducing activity of purified or recombinantly produced NLPs, among which include infiltration of purified proteins into the leaf apoplast, transpiration streams upon placing leaf petioles in protein solution, spraying protein solutions as a surfactant, and Agrobacterium-mediated transient gene expression. The Agrobacterium-mediated transient gene expression method is widely used in the literature, but this method is mainly applied to model plants, such as Nicotiana species ( Chen et al, 2021 ; Duhan et al, 2021 ). The infiltration of purified proteins method has also been used for the activity evaluation of NLPs in some forest plants ( Cobos et al, 2019 ; Hunziker et al, 2021 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%